Answers to Essential Questions About Standards, Assessments, Grading, and Reporting. - Guskey, Thomas R. (SAGE Publications, 2012)
The definitive guidebook to the complex terrain of 21st-century standards! Standards, assessments, grading, and reporting provide the foundation for nearly every initiative in modern education reform. But what do these terms actually mean? This easy-to-use Q & A gives short, simple, jargon-free answers to the questions that frequently stymie educators. Readers will come away with: A consistent vocabulary and frame of reference to share with other educators An understanding of effective implementation in all four areas Specific ideas for purposeful action Common ground that teacher.